HOVHANNES KHOSROVYAN’S WORK “THE HISTORY OF THE KUBAN CIRCASSIANS AND CIRCASSIAN ARMENIANS” - Tumanan, Lusine Sedrakovna; Abdulmazidov, Ramazan Sultanovic (History, Archeology and Ethnography of the Caucasus, 2022)
The article is dedicated to the source analysis of the work by Hovhannes Khosrovyan titled “The History of the Kuban Circassians and Circassian Armenians”, the autograph of which is currently stored in Mesrop Mashtots Institute of Ancient Manuscripts (Matenadaran). Along with a number of other Armenian sources, it has remained out researchers’ attention for a long time due to the lack of its translation into Russian. The authors of the present article participate in a joint Russian-Armenian project, within the framework of which such sources are published. “The History of the Kuban Circassians and Circassian Armenians” by Hovhannes Khosrovyan consists of separate parts, uneven in volume. In its content, the work is the travel journal of the author, who arrived to the West Caucasus for propagation of Christianity among the Circassian Armenians (Cherkesogai). After the introductory part, in which the author tells about his arrival to the Circassian Armenians, the first 12 chapters are devoted to the history, culture and character of the Circassians, and only the last small 5 chapters deal directly with the history of the Circassian Armenians. Describing the life and traditions of the Circassians, he reports on their ancient holidays, on the disagreements that arose between them during the period of adoption of Islam, on some sacred places, on campaigns in the Circassian regions of tsarist generals. As for the information about the Circassian Armenians, after outlining the history of their appearance in the Western Caucasus, he proceeds to describe the features of church rituals and their lifestyle. The work of Hovhannes Khosrovyan is important for studying the history and geography of the Adyghe peoples. Its publication in Russian planned by the authors of the article will undoubtedly enrich the source base on the history of the Circassians and Circassian Armenians.
Keywords: Circassians; Adyghe; Cherkesogai; Kuban region; Hovhannes Khosrovyan; Ubykhs; Natukhais; Shapsugs; Abadzekhs